Refugees in Germany perceived higher discrimination in the wake of the coronavirus pandemic - Adriana R. Cardozo; Christopher Prömel; Sabine Zinn (DIW Weekly Report, 2022)
Refugees in Germany perceive discrimination due to their country of origin in various life dimensions, which can negatively affect their integration into society. Using IAB-BAMF-SOEP survey data, this report analyzes to what extent refugees perceive discrimination on the labor market, at educational institutions, on the housing market, with public authorities, and in daily life. The results show that perceived discrimination increased in all observed dimensions between 2019 and 2020, especially on the labor market and at educational institutions. In 2019, refugees living in eastern Germany, refugees below 40 years old, refugees with poorer German language skills, and employed refugee women felt more discriminated against than other groups of refugees. This increase is most likely related to the abrupt changes to the labor market and to the discontinuation of important integration measures due to the coronavirus pandemic. Thus, it is essential to resume these integration measures, such as language and integration courses, as soon as possible to mitigate refugees' exclusion and marginalization.
Keywords: A14; J15; J71; Z13; 330; Perceived Discrimination; Refugees; Integration